The only plane in the sky : an oral history of 9/11 - Graff, Garrett M., 1981- (Avid Reader Press, 2019)
Over the past eighteen years, monumental literature has been published about 9/11, from Lawrence Wright<U+2019>s The Looming Tower, which traced the rise of al-Qaeda, to The 9/11 Commission Report, the government<U+2019>s definitive factual retrospective of the attacks. But one perspective has been missing up to this point<U+2014>a 360-degree account of the day told through the voices of the people who experienced it. Now, in The Only Plane in the Sky, award-winning journalist and bestselling historian Garrett Graff tells the story of the day as it was lived<U+2014>in the words of those who lived it. Drawing on never-before-published transcripts, recently declassified documents, original interviews, and oral histories from nearly five hundred government officials, first responders, witnesses, survivors, friends, and family members, Graff paints the most vivid and human portrait of the September 11 attacks yet. Beginning in the predawn hours of airports in the Northeast, we meet the ticket agents who unknowingly usher terrorists onto their flights, and the flight attendants inside the hijacked planes. In New York City, first responders confront a scene of unimaginable horror at the Twin Towers. From a secret bunker underneath the White House, officials watch for incoming planes on radar. Aboard the small number of unarmed fighter jets in the air, pilots make a pact to fly into a hijacked airliner if necessary to bring it down. In the skies above Pennsylvania, civilians aboard United Flight 93 make the ultimate sacrifice in their place. Then, as the day moves forward and flights are grounded nationwide, Air Force One circles the country alone, its passengers isolated and afraid. More than simply a collection of eyewitness testimonies, The Only Plane in the Sky is the historic narrative of how ordinary people grappled with extraordinary events in real time: the father and son working in the North Tower, caught on different ends of the impact zone; the firefighter searching for his wife who works at the World Trade Center; the operator of in-flight telephone calls who promises to share a passenger<U+2019>s last words with his family; the beloved FDNY chaplain who bravely performs last rites for the dying, losing his own life when the Towers collapse; and the generals at the Pentagon who break down and weep when they are barred from rushing into the burning building to try to rescue their colleagues.